Nucleotide Degradation of Pearl Spot during Modified Atmosphere Storage - T.K., Srinivasa Gopal; Jose, Leema; S., Manju; C.K., Kamalakanth; C.N., Ravishankar; K., Ashok Kumar (Fishery Technology, 2025)
The effect of modified atmosphere packaging (MAP) at different gas concentration on chill stored pearl spot (Etroplus suratensis Bloch) was examined by means of nucleotide degradation and sensory evaluation. K value, a quality index for fish, the ratio of the sum of inosine and hypoxanthine to the sum of ATP and related catabolites expressed as a percentage, was determined until sensory rejection during storage up to 23 days at 0 - 20C. The C02 concentration did not affect the K values of pearl spot. K value increased linearly in samples stored under air and four different modified atmospheres. Identical K values were obtained for Pearl spot packed in either aerobic or carbon dioxide modified atmosphere. K values were independent of sensory spoilage and correlate only with the length of storage of pearl spot packed under MAP.